The Past is Another Country: Designing Amnesty Law for Past Human Rights Violators - Citrawan, Harison (Indonesia Law Review, 2016)
In the context past gross human rights violation cases in Indonesia, the President’s constitutional authority to propose amnesty law might by and large implicate legal and ethical aspects. Holistically, any forgiveness and oblivion against any human rights violators should consider the development and the dynamic of international criminal law, which arguably have been directed to an absolute individual criminal responsibility. Against this issue, this paper finds that based on legal and ethical arguments, accompanied with various technical preconditions outlined in the Belfast Guideline on Amnesty and Accountability, an amnesty towards past gross human rights violators must be taken paradigmatically. Arguably, amnesty proceeding through an independent ad hoc committee shall be able to challenge Indonesia’s transitional framework, namely: to work as a historian and a jurist. This suggests that the elements of amnesty, both procedural and substantial, need to work in the area of deliberative democracy that calls for public participation and the protection of human rights.